2019
DOI: 10.1155/2019/1875435
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Vertical Position Allows Prediction of Postural Deterioration in Patients with Parkinson’s Disease

Abstract: Background. We believe that, in patients with Parkinson’s disease (PD), a forward-directed increase in the subjective vertical position (SV) leads to prolonged worsening of forward flexion of the trunk (FFT) mainly because the body adjusts to the SV. We conducted a study to clarify the relation between the SV angle, FFT angle, and various other clinical measures by comparing baseline values against values obtained 1 year later. Methods. A total of 39 PD patients (mean age, 71.9 ± 10.1 years; disease duration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Although it is not clear from this study which side of the body is most useful for measurement of lateral flexion, the contralateral SPVc ratio changes in association with LTF, so evaluation of the tilt from both sides is needed. In our previous study that examined the effect of SPV in the sagittal plane on FTF in patients with PD, we showed that the SPV in the sagittal plane affects the FTF angle over the course of the disease 11 ; in contrast to LTF and SPVc, it may be useful as a predictor of worsening of the LTF.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although it is not clear from this study which side of the body is most useful for measurement of lateral flexion, the contralateral SPVc ratio changes in association with LTF, so evaluation of the tilt from both sides is needed. In our previous study that examined the effect of SPV in the sagittal plane on FTF in patients with PD, we showed that the SPV in the sagittal plane affects the FTF angle over the course of the disease 11 ; in contrast to LTF and SPVc, it may be useful as a predictor of worsening of the LTF.…”
Section: Discussionmentioning
confidence: 95%
“…We focused on proprioceptive disintegration 28 and the resulting abnormal body schema perception 2 . It has been shown that the sagittal subjective postural vertical can be used as an index of long‐term worsening of forward bending 11 . Although recognition of the vertical position from the ipsilateral side and contralateral sides may be an indicator of the course of lateral bending, factors other than SPV in the coronal plane are needed for comprehensive evaluation of patients with LTF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard axis was a vertical line crossing L5 and descending to the oor. The axis of forward exion was de ned as the line connecting C7 and L5 observed along the sagittal plane, while the axis of lateral exion was de ned as a line connecting C7 and L5 observed along the coronal plane (11,12). SPV evaluation.…”
Section: Informed Consentmentioning
confidence: 99%
“…We also examined the SPV ratio, de ned as the SPV angle with reference to the axis of lateral exion, and we showed that the SPV ratio affects LTF. Although use of the SPV as a predictor of increased severity of postural abnormalities in patients with PD-related forward trunk exion (FTF) has been veri ed (12), effects of the SPV on the long-term clinical course of LTF have not been clari ed. Long-term follow-up is needed to clarify such effects.…”
Section: Introductionmentioning
confidence: 99%